2015
DOI: 10.1186/s13071-015-0675-y
|View full text |Cite
|
Sign up to set email alerts
|

The expression dynamics of transforming growth factor-β/Smad signaling in the liver fibrosis experimentally caused by Clonorchis sinensis

Abstract: BackgroundLiver fibrosis is a hallmark of clonorchiasis suffered by millions people in Eastern Asian countries. Recent studies showed that the activation of TGF-β/Smad signaling pathway can potently regulate the hepatic fibrogenesis including Schistosoma spp. and Echinococcus multilocularis-caused liver fibrosis. However, little is known to date about the expression of transforming growth factor-β (TGF-β) and other molecules in TGF-β/Smad signaling pathway which may play an important role in hepatic fibrosis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 34 publications
3
36
0
2
Order By: Relevance
“…In addition, the destruction of liver tissue structure caused by fibroblast proliferation and collagen deposition, and the destruction of bile duct structure that characterized with cholangiocyte hyperplasia, narrowing of bile duct lumen and periductal fibrosis were found (Figure1). These results were consistent with the typical pathological of C.sinensis infection as described in our previous research [15].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the destruction of liver tissue structure caused by fibroblast proliferation and collagen deposition, and the destruction of bile duct structure that characterized with cholangiocyte hyperplasia, narrowing of bile duct lumen and periductal fibrosis were found (Figure1). These results were consistent with the typical pathological of C.sinensis infection as described in our previous research [15].…”
Section: Discussionsupporting
confidence: 93%
“…TGF‐β/Smad signalling is a canonical pathway which potently regulates tissue fibrogenesis . TGF‐β1 is known to play a central role in the pathogenesis and progression of renal fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that TGF-β/Smad signaling plays a crucial role in the progression of hepatic fibrosis caused by parasitic infection, including Schistosoma , Clonorchis sinensis , and Echinococcus multilocularis , as well as other etiological factors[79,80]. More specifically, TGF-β1 ligation to TGF-β type I (TGFβRI) and type II receptors induces Smad2/3 phosphorylation and its subsequent interaction with Smad4.…”
Section: Novel Therapeutic Targets In Liver Fibrosismentioning
confidence: 99%